2007
DOI: 10.1016/j.bcp.2006.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-7-catalyzed release of HB-EGF mediates deoxycholyltaurine-induced proliferation of a human colon cancer cell line

Abstract: Prior evidence indicates that bile acids stimulate colon cancer cell proliferation by muscarinic receptor-induced transactivation of epidermal growth factor receptors (EGFR). To explore further the mechanism underlying this action, we tested the hypothesis that bile acids activate a matrix metalloproteinase (MMP) that catalyzes release of an EGFR ligand. Initial studies showed that nonselective MMP inhibitors blocked the actions of deoxycholyltaurine (DCT), thereby indicating a role for MMP-catalyzed release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
94
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 46 publications
(86 reference statements)
11
94
0
Order By: Relevance
“…This observation is consistent with our in vitro observations in human colon cancer cells that post-M 3 R/EGFR signaling is mediated primarily by the proproliferative ERK pathway and that blocking ERK signaling abolishes M 3 R-agonist-induced cell proliferation (8,(11)(12)(13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with our in vitro observations in human colon cancer cells that post-M 3 R/EGFR signaling is mediated primarily by the proproliferative ERK pathway and that blocking ERK signaling abolishes M 3 R-agonist-induced cell proliferation (8,(11)(12)(13).…”
Section: Discussionsupporting
confidence: 92%
“…These actions of acetylcholine are blocked by muscarinic receptor inverse agonists, calcium chelators, and inhibitors of mitogen-activated protein/ERK kinase (the regulatory protein just upstream of ERK), and they do not occur in SNU-C4 human colon cancer cells that do not express M 3 R (9). Moreover, recent studies support the hypothesis that luminal bile acids, long associated with the development of colon cancer (10), also stimulate colon cancer cell proliferation by M 3 R-and epidermal growth factor receptor-dependent mechanisms (11)(12)(13). In these in vitro cell systems, proliferative actions of muscarinic agonists require both M 3 R expression and activation of post-M 3 R signaling.…”
Section: Introductionmentioning
confidence: 71%
“…Conjugated secondary bile acids induce proliferation of colon cancer cells by a mechanism involving MMP7-catalyzed release of an EGFR ligand, HBEGF (9). Because bile acids interact functionally with muscarinic receptors and induce transactivation of EGFR (7,9,26), we hypothesized that the actions of ACh were mediated by a similar mechanism.…”
Section: Ach-induced Proliferation Of H508 Cells Is Mediated By Mmp7-mentioning
confidence: 99%
“…Hence, there is great interest in identifying key colon cancer growth factors and their receptors. Increasing evidence indicates that muscarinic receptors and ligands play key roles in intestinal neoplasia (8,9,14,15,17,27). The muscarinic cholinergic family of G proteincoupled receptors (GPCRs) consists of five muscarinic receptor subtypes designated M 1 R, M 2 R, M 3 R, M 4 R, and M 5 R (for reviews see Refs.…”
mentioning
confidence: 99%
“…Matrilysin is tightly associated with cell surface heparan sulfated proteoglycans (Yu and Woessner 2000), and this interaction localizes the proteinase with heparin-binding matrilysin substrates such as heparin-binding epidermal growth factor and C type lectin member family member 3A (Yu et al 2002;Cheng et al 2007;Lynch et al 2007;Tsunezumi et al 2009). Bone morphogenetic protein (BMP-7) and hepatocyte growth factor (HGF) are heparin-binding proteins that are critical in normal renal development (Davies and Fisher 2002;Irie et al 2003;Takada et al 2003), and our prior microarray study demonstrated that BMP7 gene expression and BMP-7 tissue levels were reduced in dysplastic kidneys compared to normal controls (Jain et al 2007).…”
mentioning
confidence: 99%